Intergovernmental relations in federal and unitary nations: a framework for analysis - Chakunda, Vincent; Ogochukwu, Nzewi (International Knowledge Sharing Platform, 2020)
This paper applies the value-neutral empirical study approach to examine intergovernmental relations (IGR) in two federal states (the US and Nigeria) and two unitary states (UK and South Africa) using a framework for comparative analysis developed by the authors. The paper presents country studies examining the formal institutional arrangements and their operation in practice, to enable the IGR systems and frameworks in these countries to be sufficiently understood. The four triangulated case studies reflect on convergent and divergent views of the state of IGR in the different nations, the lines of differences and the prevailing views. Each multilayered state has its own system of intergovernmental relations. This system reflects on each case a specific constitutional set up and a specific political history. This paper therefore relates the different constitutional and political regimes and attempts to define generalisable similar trends. The comparative exploration of IGR in the four countries is therefore placed within the larger social and political context of the relationships, both conflictual and consensual, that shape the underlying dynamics of political issues. Hence country studies presented here will not merely describe IGR, but articulate the constitutional/legalistic, institutional, political, socio-economic, and cultural sources of each of the studied nation’s patterns of IGR. The thrust is to reflect on the ethno-cultural cleavages and the influence of regional units in shaping IGR and explain the nature of IGR across different policy fields.